2013
DOI: 10.1371/journal.pone.0059714
|View full text |Cite
|
Sign up to set email alerts
|

Massive Sorghum Collection Genotyped with SSR Markers to Enhance Use of Global Genetic Resources

Abstract: Large ex situ collections require approaches for sampling manageable amounts of germplasm for in-depth characterization and use. We present here a large diversity survey in sorghum with 3367 accessions and 41 reference nuclear SSR markers. Of 19 alleles on average per locus, the largest numbers of alleles were concentrated in central and eastern Africa. Cultivated sorghum appeared structured according to geographic regions and race within region. A total of 13 groups of variable size were distinguished. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
7
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 55 publications
(77 reference statements)
3
93
7
4
Order By: Relevance
“…S4A) (F ST = 0.06, P < 0.01) was all relatively weak compared with the differentiation among the populations inferred with InStruct (n = 143 with Q > 0.90) (F ST = 0.21, P < 0.01). Moreover, as in other continent-wide assessments (9,12) we found that the differentiation among accessions belonging to the five discrete basic races (n = 82) was relatively weak (F ST = 0.13, P < 0.01) compared with the differentiation among the inferred populations. Thus, social and cultural factors reflected in the distribution of language families appear to be the strongest structuring factors behind the continent-wide pattern.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…S4A) (F ST = 0.06, P < 0.01) was all relatively weak compared with the differentiation among the populations inferred with InStruct (n = 143 with Q > 0.90) (F ST = 0.21, P < 0.01). Moreover, as in other continent-wide assessments (9,12) we found that the differentiation among accessions belonging to the five discrete basic races (n = 82) was relatively weak (F ST = 0.13, P < 0.01) compared with the differentiation among the inferred populations. Thus, social and cultural factors reflected in the distribution of language families appear to be the strongest structuring factors behind the continent-wide pattern.…”
Section: Resultssupporting
confidence: 86%
“…An obvious caveat in our case is that, during both the 1983 collecting and the 2010/2013 collecting of nyithin, we were unable to sample the full range of landraces included in the nyithin landrace complex in the Pari folk taxonomy. Furthermore, ex situ conserved accessions have undergone purification and forced selfing during regeneration (9), resulting in reduced heterozygosity compared with the original landrace. Thus, we limit our inference of the detected patterns to say that there is no evidence for loss of genetic diversity within nyithin.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, since the collection in 1999, the accessions have been regularly regenerated by enforced self-pollination. Billot et al (2013) found similar result on a collections maintained by self-pollination. In contrast, high Ho value (0.11) was observed by Barnaud et al (2007) when assessing samples obtained directly from landraces.…”
Section: Discussionsupporting
confidence: 73%
“…The diversity was higher than that (He=0.37) reported by Barro-Kodombo et al (2008) on grain sorghum and slightly below the value (0.47) reported by Nebie (2014) on sweet stem sorghum. The genetic diversity values (0.674 and 0.61 respectively) reported by Billot et al (2013) and Sawaodgo (2015) were all beyond the values found in the present study. This weak diversity may be due to the relatively small number of accessions used here compared to the large number (3367) used by Billot et al (2013).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation